Extrahepatic Bile Duct Hepatocellular Carcinoma without Primary Hepatic Parenchymal Lesions: — A Case Report — - Cho, Hyeon Geun (Korean J Intern Med, 1996)
Obstructive jaundice is rarely a presenting symptom of hepatocelluar carcinoma (HCC). Most of the cases in the literature describing obstructive jaundice by HCC have a major hepatic component. Extrahepatic HCCs without primary hepatic parenchymal lesions are extremely rare. We encountered a case of extrahepatic HCC without primary hepatic parenchymal lesions in a 36-year-old man who presented with jaundice. We extensively sought primary hepatic parenchmal lesions preperatively and postoperatively with hepatic angiography and combined computed tomography (CT) studies, such as CT arterioportography and lipiodol-CT. The patient has been followed up for 1 year without definite evidence of recurrence. We herein report an unusual manifestation of HCC.